A digitális jegybanki pénz dilemmái és trilemmái - Kutasi, Gábor (Public Finance Quarterly, 2022)
Dirk Niepelt (szerk)Central Bank Digital Currency: Considerations, Projects, OutlookLondon, CEPR Press, 2021